2021
DOI: 10.1029/2021jc017331
|View full text |Cite
|
Sign up to set email alerts
|

On the Physical Settings of Ice Bridge Formation in Nares Strait

Abstract: The ice bridge that forms seasonally across Nares Strait impedes the southward transport of sea ice from the Lincoln Sea to Baffin Bay and contributes to the maintenance of the North Water Polynya. Previous studies have quantified how the bridge affects ice export and highlighted a long term decline in the duration of the bridge; however, the specific mechanism by which the bridge forms has remained unstudied. In this study we first used a mix of satellite imagery to refine the timing of formation for the 16 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Kirillov et al. (2021) used a mixed data set of satellite images (MODIS/SAR) to analyze the formation of the ice arch at the Smith Sound during 2000/2001–2020/2021 and indicated that in most years the formation of the ice arch was 3 days (on the average) earlier than reported in Vincent (2019). This was caused by using different data and methods as well as changes in atmospheric and oceanic forcing.…”
Section: Introductionmentioning
confidence: 99%
“…Kirillov et al. (2021) used a mixed data set of satellite images (MODIS/SAR) to analyze the formation of the ice arch at the Smith Sound during 2000/2001–2020/2021 and indicated that in most years the formation of the ice arch was 3 days (on the average) earlier than reported in Vincent (2019). This was caused by using different data and methods as well as changes in atmospheric and oceanic forcing.…”
Section: Introductionmentioning
confidence: 99%
“…for a relatively immobilized ice cover that coalesces under cold air temperatures, which is similar to the process that facilitates the formation of the ice bridge in Nares Strait (Kirillov et al, 2021). An estimated 24 cm of new ice rapidly forms on the western side of the channel and locks the bridge in place.…”
Section: Discussionmentioning
confidence: 92%
“…An important factor for the consolidation of an ice bridge is the existence of an ice cover that is thick enough and therefore strong enough to oppose external forcing once it has consolidated (Sodhi, 1977;Kubat et al, 2006;Rallabandi et al, 2017;Kirillov et al, 2021). If the ice cover is too thin it may consolidate, but it will simply be too weak to oppose external forcing and break up once wind speeds increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that care must be taken when interpreting studies that use the ERA5 reanalysis to characterize the wind field's role in ice motion along the strait (Kirillov et al., 2021; Shokr et al., 2020). In particular, the ERA5's underestimation of both mean and extreme windspeeds along the strait is cause for concern as is its inability to represent features such as the gradient in windspeed across Kane Basin.…”
Section: Discussionmentioning
confidence: 99%